Sustainable community participation in homestay program - Wan Abd Aziz, Wan Mohd Amin; Yahaya, Ibrahim (Medwell Journals, 2016)
This study explores the emergence and possibilities of sustainable community participation in the homestay program as a new approach in the tourism industry in Malaysia. This study focusses on the assessing the relationship between community participation, attitude and sustainable development in the homestay program. This research uses a path-model survey to acquire the causal relationships and multiple regressions to verify the adjusted R2 with the data derived from 306 homestay participants in Malaysia. The result found that the first layer of the path diagram indicate 16.1% of variance attitude was determined by factors involving community participation and 31.1% of sustainable development was determined by community participation and attitude. The findings imply that attitude emerges as a prominent intermediary and moderating variable in discerning the relationship between community participation and sustainable development. Finally, the results indicated that the community participation is a crucial factor in developing sustainable development in the homestay program.